Molding and moving bodies in a neoliberal world: African football labor migrants in Egypt - Groves, Andrea (AUC Knowledge Fountain, 2012)
Egypt has a large profitable football industry that increasingly attracts the attention of both football agents wanting to earn income from another market and sub-Saharan football players hoping to further a career by using Egypt as an intermediary between their home countries and Europe. The labor migration of sub-Saharan football players to Egypt has been enabled mainly by neoliberal, market-orientated changes adopted by FIFA, the CAF, the European Union, and the Egyptian football industry itself. Yet more importantly it is the individual actors that implement and take advantage of these hegemonic spheres of influence. This thesis explores how these individual actors and sub-Saharan football players have negotiated the neoliberal project. Specifically it shows the changes brought by localized mutations of neoliberalism as well as its continuities how they affect the ways in which sub-Saharan football players in Egypt move, work, and live.